Employer Satisfaction with Polytechnic Graduate: Comparison Between Industry Cluster - Husnira binti Hussin; Rusdi bin Rusli; Wan Mohd Zawawi bin Wan Yunus (IJESEMS : International Journal of Engineering Science Educatioon and Management System, 2020)
The work environment is changing from time to time in line with the introduction of new technology. Industrial Revolution 4.0 (IR4.0) forces education providers to identify the characteristics of future workers' needs by the industry. To fulfill this demand, polytechnic created a close relationship with industry through conducting many programs such as dialog between industry and polytechnic, CEO@Faculty, the industry in campus and employer satisfaction study with polytechnic graduate. However, previous studies compared employer satisfaction among industry clusters are very limited. The objective of this study was to examine employer satisfaction with Politeknik Sultan Mizan Zainal Abidin (PSMZA) graduate and to compare employer satisfaction between industry clusters. A total of 112 employers from three main engineering clusters; mechanical (46%), electrical (30%) and civil (24%) involved in this study. This study used two-step analysis: Kruskal-Wallis test was used to identify differences for three industry clusters; mechanical, electrical and civil engineering and Post Hoc test performs to identify the detail differences between each cluster. The results show that employers in the mechanical engineering cluster are less satisfied with PSMZA graduates compared to employers in civil engineering clusters for computer skills in processing information. This study also found that compared to employers in the electrical engineering cluster, employers in the mechanical cluster are less satisfied with PSMZA graduates related to proficiency in the English language. In terms of entrepreneurship skills, employers in the mechanical cluster found less satisfaction with a graduate from PSMZA compared to employers in the electrical cluster. Findings from this study can be used by the department as a guide in revising their curriculum in the future.